Forecasting The Budget Deficit as A Method of Ensuring the Financial Security of the State - Makhanets, Liubov (European Journal of Sustainable Development, 2025)
Budget deficit represents a crucial measure of the country's economic health while having important geopolitical meaning in the modern world. The importance of the topic under consideration comes from the demand for efficient management of public finances to make a country financially resilient. This study sets out the objective of predicting Ukraine's budget deficit based on exponential advection and acceleration analysis methods. The statistics to use are provided by the State Statistics Service of Ukraine and the Ministry of Finance of Ukraine. The findings revealed that the increase in Ukraine’s budget deficit due to incorrect and unsystematic actions can have fatal consequences for international economic activity. The study's practical significance lies in outlining recommendations for using forecast results in the management of public finance to minimise the negative impact of the deficit on the economy. The models proposed can be implemented in current fiscal planning structures to measure accuracy in forecasts. Keywords: budget deficit, forecasting, exponential smoothing, acceleration analysis, foreign economic activity, financial stability